Motivational Interviewing to Support Oral AntiCoagulation adherence in patients with non-valvular Atrial Fibrillation (MISOAC-AF): a randomised clinical trial. (25th November 2020) - Tzikas, A; Samaras, A; Kartas, A; Vasdeki, D; Fotos, G; Dividis, G; Paschou, E; Forozidou, E; Tsoukra, P; Kotsi, E; Goulas, I; Karvounis, H; et al.
Abstract: Background: Oral anticoagulation (OAC) is paramount to effective thromboprophylaxis; yet adherence to OAC remains largely suboptimal in patients with atrial fibrillation (AF). Purpose: We aimed to assess the impact of an educational, motivational intervention on the adherence to OAC in patients with non-valvular AF. Methods: Hospitalised patients with non-valvular AF who received OAC were randomly assigned to usual medical care or a proactive intervention, comprising motivational interviewing and tailored counseling on medication adherence. The primary study outcome was adherence to OAC at 1-year, evaluated as Proportion of Days Covered (PDC) by OAC regimens and assessed through nationwide prescription registers. Secondary outcomes included the rate of persistence to OAC, gaps in treatment, proportion of VKA-takers with labile INR (defined as time to therapeutic range<70%) and clinical events. Results: A total of 1009 patients were randomised, 500 in the intervention group and 509 in the control group. At 1-year follow-up, 77.2% (386/500) of patients in the intervention group had good adherence (PDC>80%), compared with 55% (280/509) in the control group (adjusted odds ratio 2.84, 95% confidence interval 2.14–3.75; p<0.001). Mean PDC±SD was 0.85±0.26 and 0.75±0.31, respectively (p<0.001). Patients that received the intervention were more likely to persist in their OAC therapy at 1 year, while usual medical care was associated with more major (≥3 months) treatment gaps [Figure]. Among 212 VKA-takers, patients in the intervention group were less likely to have labile INR compared with those in the control group [21/120 (17.1%) vs 34/92 (37.1%), OR 0.33 95% CI 1.15–0.72, p=0.005]. Clinical events over a median follow-up period of 2 years occurred at a numerically lower, yet non-significant, rate in the intervention group [Table]. Conclusions: In patients receiving OAC therapy for non-valvular AF, a motivational intervention significantly improved patterns of medication adherence, without significantly affecting clinical outcomes. Funding Acknowledgement: Type of funding source: None